Antibacterial Activity of Gold Nanoparticles against Bacteria Isolated from Diabetic Foot Infections - Jafar, Razeghi; R., AL-Turaihi Mohammed; Al shammari, Hassan hadi (Journal of Science in Medicine and Life, 2025)
Diabetic foot ulcers (DFUs) are among the most important challenges in diabetes mellitus (DM) patients that are linked to a higher risk of morbidity and death in these patients. Specifically, antibiotic resistance in DFUs is essential for efficient management and treatment of infected wounds. The current study was aimed to evaluate the activity of gold nanoparticles (Au NPs) against multidrug-resistant bacterial isolates from diabetic foot infections in Najaf city. The study was carried out in the Al-Hakem hospital from January 2021 to July 2022. Totally, 150 samples were taken from diabetic foot infections of patients who were admitted to different hospitals (Al-Hakeem General Hospital and Al-Zahraa Teaching Hospital) in AL-Najif AL-Ashraf city. Diagnosis of bacteria and antibiotic susceptibility test was carried out for all isolates using Vitek 2 instrument. Au NPs were synthesized using the green synthesis method using bacteria Bacillus subtilis was cultured then incubated in shaking then centrifuged and 100 μl of 1 M HAuCl4 (Sigma Aldrich, USA) solution was added to 100 ml of the obtained microbial supernatant then incubated in a shaker incubator .The successful preparation of AuNPs was detected by Ultraviolet–visible spectroscopy( the AuCl4 had been reduced to gold nanoparticles, which can be distinguished by the peak at 650 nanometers detected in the spectrum, Atomic Force Microscopy (AFM)Also, the results indicated proper synthesis, and Fourier Transform Infrared Spectroscopy (FTIR).The FT-IR spectrum of the Au NPs shows different bands at 3418.39, 2088.60, 1639.93, 1407.05, 1084.52, 706.75 and 658.36 cc. The antibacterial activity of AuNPs was examined against three types of bacterial isolates including P. auerginosa, E.coli and Staph aureus. The concentrations that were used in this assay were 100 μg/mL, 50 μg/mL and 25 μg/mL (serial dilution) were used. The results showed the most bacteria isolated from foot diabetic infections were Staphylococcus aureus (64.8%), Pseudomonas aeruginosa (14.8%) and E.coli (14.8%). Antibacterial effects of Au NPs were established in the all concentration ranges of this study. Besides, the bactericidal potential of NPs were dose dependent where the highest and lowest antibacterial activity were observed in the NPs concentration of 100 µg/ml and 25 µg/ml, respectively. The findings indicated killing rate of 77.1%, 77.0%, 76.8% against isolated Pseudomonas auerginosa, E.coli and Staph aureus in 100 µg/ml of NPs, respectively. However antibacterial activity were 32.2%, 37.0%, and 28.1% in 25 µg/ml concentrations for the same order of bacterial species.25 µg/ml concentrations of Au NPs showed antibacterial activity between 32.2%, 37.0%, and 28.1% against isolated pseudomonas aeruginosa, E.coli and Staph aureus. The current study concluded the AuNPs antibacterial have higher activity against bacterial isolates Pseudomonas aeruginosa, E.coli and Staph aureus. The antioxidant activity to AuNPs is effective, and compared to other elements, gold also proved to be highly effective against oxidation, so it is considered an effective element in medical applications. The hemolytic activity of gold nanoparticles in whole blood (ex vivo) showed very low hemolytics.